Chart Customization for Developing Decision Support System at Petra Christian University - Siget Wibisono; Rolly Intan; Yulia - (Jurnal Infra, 2015)
Academic records of student candidates and students of Petra Christian University (PCU) which have been stored so far have not been used to generate information. PCU’s Top-level management needs a way to generate information from the records. The generated information is expected to support the decision-making process of Top-level management.Before starting the application development, analysis and design of the student academic records and the needs of Top-level management are done. The design stage produces a number of modeling that will be used to create the application.The final result of the development is an Academic Decision Support System application for PCU. The developed application includes Extract, Transform, and Load (ETL), customizable graphs, and user maintenance features.